Update on protease-activated receptor 2 in inflammatory and autoimmune dermatological diseases - Xu, Kejia; Wang, Lin; Lin, Mao; He, Gu (Frontiers in Immunology, 2024)
Protease-activated receptor 2 (PAR2) is a cell-surface receptor expressed in various cell types, including keratinocytes, neurons, immune and inflammatory cells. Activation of PAR2, whether via its canonical or biased pathways, triggers a series of signaling cascades that mediate numerous functions. This review aims to highlight the emerging roles and interactions of PAR2 in different skin cells. It specifically summarizes the latest insights into the roles of PAR2 in skin conditions such as atopic dermatitis (AD), psoriasis, vitiligo and melasma. It also considers these roles from the perspective of the cutaneous microenvironment in relation to other inflammatory and autoimmune dermatological disorders. Additionally, the review explores PAR2's involvement in associated comorbidities from both cutaneous and extracutaneous diseases. Therefore, PAR2 may serve as a key target for interactions among various cells within the local skin environment.